2019
DOI: 10.3389/fnins.2019.00639
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Acoustic Information in Lexical Tone Production and Perception by Pediatric Cochlear Implant Recipients

Abstract: Purpose: This study examined the utilization of multiple types of acoustic information in lexical tone production and perception by pediatric cochlear implant (CI) recipients who are native speakers of Mandarin Chinese. Methods: Lexical tones were recorded from CI recipients and their peers with normal hearing (NH). Each participant was asked to produce a disyllabic word, yan jing , with which the first syllable was pronounced as Tone 3 (a low dipping t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…Supplementary Table 3 summarises the eleven studies concerned with tone production by Mandarin-speaking children with CIs (Chuang et al 2012;Han et al 2007;Li et al 2018;Mao, Chen, and Xu 2017;Peng, Tomblin, et al 2004a;Xu et al 2004;Xu et al 2011;Zhou and Xu 2008;Zhou et al 2013;Deroche et al 2019;Tang et al 2019b). They either involve judgments of accuracy by professional speech pathologists and lay native speakers or objective measures.…”
Section: Tone Production In Children With Cismentioning
confidence: 99%
See 1 more Smart Citation
“…Supplementary Table 3 summarises the eleven studies concerned with tone production by Mandarin-speaking children with CIs (Chuang et al 2012;Han et al 2007;Li et al 2018;Mao, Chen, and Xu 2017;Peng, Tomblin, et al 2004a;Xu et al 2004;Xu et al 2011;Zhou and Xu 2008;Zhou et al 2013;Deroche et al 2019;Tang et al 2019b). They either involve judgments of accuracy by professional speech pathologists and lay native speakers or objective measures.…”
Section: Tone Production In Children With Cismentioning
confidence: 99%
“…However, there are few studies that have examined speech production in Mandarin-speaking children with CIs, with most published work focussing on expressive vocabulary development and speech intelligibility (Han et al 2007;Li et al 2020). Where studies do report speech production measures in Mandarinspeaking children with CIs, they often show conflicting results and are based on different materials and methods (Chuang et al 2012;Deroche et al 2019;Han et al 2007;Mao, Chen, and Xu 2017;Tseng, Kuei, and Tsou 2011). For instance, Han et al (2007) reported that Mandarin-speaking children with CIs performed better on T3 than T2 using a perceptual analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, while such a distorted map/internal representation may help CCIs to learn to correctly identify and discriminate vocal emotions, it may not be their best guide as they learn to produce the same emotions (particularly in such a way as to be understood by NH conversational partners). For example, a recent study by Deroche et al (2019) found that CCIs' productions of lexical tones focused on contrasting the secondary cue (duration), while CNHs' productions focused on voice pitch changes. Additionally, they found that CCIs' emphasis on the voice pitch cue in their productions was inversely related to their reliance on the duration cue in the perception domain: CCIs who relied more on the duration cue in perception, emphasized the voice pitch cue less in production.…”
Section: Talker-related Factors: Early Auditory Experiencementioning
confidence: 99%
“…In a group of school-age CCIs aged 6-12 years, Van de Velde et al 2019found a correlation between emotion recognition and production by CCIs. In speakers of tonal languages, moderate correlations have been reported between the perception and production of lexical tones (Deroche, Lu, Lin, Chatterjee, & Peng, 2019;Xu et al, 2011;Zhou, Huang, Chen, & Xu, 2013). Lexical tones are contrasted primarily by voice pitch and its changes, with duration cues playing a secondary role.…”
mentioning
confidence: 99%
“…The F0 contours are (1) high and flat, (2) low at the beginning and then rising, (3) falling at the beginning and then rising with a dip in the middle, and (4) high-falling, respectively. Such tonal information, primarily carried by the F0, is not adequately coded in current CI devices ( Han et al, 2009 ; Xu and Zhou, 2011 ; Limb and Roy, 2014 ; Deroche et al, 2019 ). Previous studies that focused on tone perception have revealed significant deficits of CI children in tone recognition tasks, with tremendous variability observed across CI subjects ( Lee et al, 2002 ; Peng et al, 2004 ; Han et al, 2009 ; Zhou et al, 2013 ; Mao and Xu, 2017 ; Holt et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%